Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2008
DOI: 10.1145/1357054.1357058
|View full text |Cite
|
Sign up to set email alerts
|

From meiwaku to tokushita !

Abstract: Based on ethnographically-inspired research in Japan, we report on people's experiences using digital money payment systems that use Sony's FeliCa near-field communication smartcard technology. As an example of ubiquitous computing in the here and now, the adoption of digital money is found to be messy and contingent, shot through with cultural and social factors that do not hinder this adoption but rather constitute its specific character. Adoption is strongly tied to Japanese conceptions of the aesthetic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 6 publications
2
19
0
Order By: Relevance
“…In this category of interfaces, NFC is used for creating digital service access points. Simple examples of service interfaces include RFID-based public transportation ticketing [10] and mobile payment [1] solutions, where a touch of the reader transfers the action into the background system that then validates and processes the transaction.…”
Section: Service Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this category of interfaces, NFC is used for creating digital service access points. Simple examples of service interfaces include RFID-based public transportation ticketing [10] and mobile payment [1] solutions, where a touch of the reader transfers the action into the background system that then validates and processes the transaction.…”
Section: Service Interfacesmentioning
confidence: 99%
“…It has been found to be a cheap, simple and relatively robust technology for applications ranging from m-commerce (mobile commerce) in Japan [1] to cattle management in Australia [2]. In recent years, there has been interest in and efforts to integrate RFID readers into standard mobile phones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, despite some notable exceptions (e.g. [5,6,8]), researchers in HCI have largely resisted the topic of money: this despite a rich literature in economic sociology, ICT4D [ [6]], anthropology, business IT, and science and technology studies on the subject. Such studies have shown that monetary transactions are part of nearly all social institutions, including marriage, birth and death [ [7], [9]].…”
Section: Introductionmentioning
confidence: 99%
“…The study of money and its exchange is therefore also a study of how meaning and value are assigned by those who use it. This idea can be leveraged to support design; for example, Mainwaring et al's ethnographic studies of digital money use shows how cultural aspects can be leveraged to design mobile payment systems that fit with the context of its users [ [5]]. In this workshop, then, we hope to bring this rigorous multi-disciplinary work into conversation with HCI to produce novel understandings of the role of money in contemporary computing environments.…”
Section: Introductionmentioning
confidence: 99%